The Birds of Indonesia, Kukila Checklist No. 1: Additions, corrections and notes - 2 - Holmes, Derek A; Bishop, K David; Andrew, Paul (KUKILA, 2000)
This is the second update of the Kukila Checklist of the birds of Indonesia. The authorship of these checklist updates will be the Ornithological Society of Indonesia, or Kukila for ease of reference. The inaugural checklist was published in 1992 (Andrew 1992) and the first update appeared a year later (Andrew 1993). This second supplement is organized in the same way except that the many issues of classification that have been published since 1993 will be desk with in a separate paper that is currently in preparation. The main objective of the present paper is to present new distributional data. Most of the data are derived from published references, although a few are from submitted notes that await publication.